2016
DOI: 10.1021/jacs.6b08161
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Approach to Identify Heparan Sulfate Ligand Requirements of Robo1

Abstract: An integrated methodology is described to establish ligand requirements for heparan sulfate (HS) binding proteins based on a workflow in which HS octasaccharides are produced by partial enzymatic degradation of natural HS followed by size exclusion purification, affinity enrichment using an immobilized HS-binding protein of interest, putative structure determination of isolated compounds by a hydrophilic interaction chromatography–high-resolution mass spectrometry platform, and chemical synthesis of well-defin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 45 publications
(42 citation statements)
references
References 57 publications
2
40
0
Order By: Relevance
“…Our finding that enoxaparin, a partially depolymerized heparin with an average molecular weight of ~4.5 kDa, has lower potency than UFH (average molecular weight ~15 kDa) even in terms of mg/L is consistent with previous SPR results (5), as well as SPR results presented here ( Figure 6). The lower potency and higher K D of the partially depolymerized heparin is consistent with a binding interaction that involves multiple binding sites on each UFH polysaccharide molecule, which we have also found in some of our previous studies of protein-GAG interactions (26,27). These results are also consistent with previous sequence analysis of the S protein of SARS-CoV-2, which suggests the possibility of multiple heparin binding sites (5), as well as experiments with the receptor binding domain of the S-protein, which showed binding at ~40x lower affinity (7) possibly due to the lack of avidity from binding sites in other domains.…”
Section: Discussionsupporting
confidence: 88%
“…Our finding that enoxaparin, a partially depolymerized heparin with an average molecular weight of ~4.5 kDa, has lower potency than UFH (average molecular weight ~15 kDa) even in terms of mg/L is consistent with previous SPR results (5), as well as SPR results presented here ( Figure 6). The lower potency and higher K D of the partially depolymerized heparin is consistent with a binding interaction that involves multiple binding sites on each UFH polysaccharide molecule, which we have also found in some of our previous studies of protein-GAG interactions (26,27). These results are also consistent with previous sequence analysis of the S protein of SARS-CoV-2, which suggests the possibility of multiple heparin binding sites (5), as well as experiments with the receptor binding domain of the S-protein, which showed binding at ~40x lower affinity (7) possibly due to the lack of avidity from binding sites in other domains.…”
Section: Discussionsupporting
confidence: 88%
“…Coincidently, a previous experiment on exposing Xenopus embryonic brains to selectively desulfated heparins followed by assessing their mistargeting-inducing activity suggest that the minimum size of HS required for mistargeting is dp8 [57]. Another previous study based on separation and sequencing of Robo1-bound, natural derived HSs also identified a dp8 as a potential ligand for this interaction, despite that the detailed sulfation patterns are different from the dp8 used in this study [58]. Taken together with our observation that a HS dp8 has the highest binding affinity towards Robo1 when competing with longer, more sulfated HSs suggest that the binding epitope on Robo1 could be a shallow grove which prefers to accommodate a HS dp8.…”
Section: Resultsmentioning
confidence: 49%
“…A previous SPR study that measured the competition between chip immobilize heparin and selectively desulfated heparin-derived oligosaccharides in solution demonstrate that N- sulfation and 6-O sulfation contribute more to Robo1-Slit interaction than 2-O sulfation [56]. Another study which measured the binding affinity of chip immobilized Robo1 and a series of chemically modified HS dp4 suggest that 2-O sulfation have a negative effect on the interaction [58].…”
Section: Resultsmentioning
confidence: 99%
“…43 Indeed, the use of oligosaccharides decorated with lanthanide-binding tags has arisen as new NMR protocols to unravel the 3D shape of complex glycans and to afford key elements for unraveling fine details of their interactions. 44 From the physics perspective, the origin of this methodology is perfectly established. The occurrence of a paramagnetic nucleus in a molecule generates strong chemical shift variations, pseudo-contact shifts 45 (PCS), in the NMR resonance signals of its adjacent nuclei.…”
Section: Use Of Paramagnetic Nmrmentioning
confidence: 99%